An empirical analysis of seasonal anomalies in Chinese Stock Market - Zhang, Wei (2010)
This study investigates the seasonal regularities in Chinese stock market, practically tests the existence of the day-of-the-week effect and January effect in Shanghai Composite Index, Shenzhen Composite Index and Shanghai-Shenzhen 300 Index. A sample data from July 1 1994 to December 31 2008 of Shanghai Composite Index and Shenzhen Composite Index, and from April 8 2005 to December 31 2008 for Shanghai-Shenzhen 300 Index. Observation of test is based on no-price-limit period, price-limit period and bullish period to against the whole period. The finding indicates that Shanghai-Shenzhen 300 index is more volatile than the other two indices and it is more correlated with Shanghai Composite index rather than Shenzhen Composite index. Results confirmed highest return on Thursday on three indices and an evidence of ‘reverse’ Monday and weekend effects on both exchanges. January effect only exists in no-price-limit period and price-limit period for both exchanges.